دلالة اللباس المناسباتي في الموروث الشعبي العرس٬ الختان٬ الحج٬ العدة٬ الطقوس - خديجة بلقاسمي; حيـــــــــــاة عطالله; صبرينـــــة زوزو (University of El-oued, 2025)
تسلط هذه الدراسة الضوء على اللباس المناسباتي للمرأة السوفية في منطقة الوادي، من خلال لباس بدنها المتمثل في الحولي تحديدا، مع التطرق إلى طريقة ومواد وتقنيات انجازه وألوانه، ولم تقتصر الدراسة على ذلك فقط، فقد تطرقت إلى تخصيص جزء كنبذة تاريخية عن المنطقة وابراز عاداتها وتقاليدها في عدة مجالات إجتماعية وثقافية.... وكذا بينت الدراسة الدلالة الرمزية للباس المناسباتي الخاص بالمرأة السوفية، ومدى محافظة المرأة السوفية على الموروث الثقافي من خلال زيها التقليدي المتمثل في الحولي السوفي This study sheds light on the ceremonial dress of Soufi women in the ELoued region, specifically through their body garment, the Hawli, while addressing the methods, materials, techniques, and colors of its production. The study not only focuses on this aspect, but also provides a historical overview of the region and highlights its customs and traditions in several social and cultural domains. The study also demonstrates the symbolic significance of Soufi women's ceremonial dress and the extent to which Soufi women preserve their cultural heritage through their traditional dress, the Soufi Hawli
مذكرة .ماستر . أدب شعبي . 2025
Keywords: الثقافة، الموروث، الحولي، اللباس، المناسباتي، السوفية، المرأة; culture; heritage; Hawli; dress; ceremonial; Soufi; women